Cattaneo-Christov Heat Flux on an MHD 3D Free Convection Casson Fluid Flow Over a Stretching Sheet - SHANKAR, D. Gowri; RAJU, C.S.K.; KUMAR, M.S. Jagadeesh; MAKINDE, Oluwole Daniel (Engineering Transactions, 2020)
In this investigation, we analyze the magnetohydrodynamic (MHD) three-dimensional (3D) flow of Casson fluid over a stretching sheet using non-Darcy porous medium with heat source/sink. We also consider the Cattaneo-Christov heat flux and Joule effect. The governing partial differential equations (PDEs) are transformed into ordinary differential equations (ODEs) using suitable transformations and solved by using the shooting technique. The effects of the non-dimensional governing parameters on velocity and temperature profiles are discussed with the graphs. Also, the skin friction coefficient and Nusselt number are discussed through tables. We also validate our results with the ones already available in the literature. It is found that the obtained results are in excellent agreement with the existing studies under some special cases. Our analysis reveals that the thermal relaxation parameter reduces the temperature field for the Newtonian and non-Newtonian fluid cases. It is also found that the temperature profile is decreased in the Newtonian fluid case when compared with the non-Newtonian fluid case.